PEMBERDAYAAN KELOMPOK SADAR WISATA (POKDARWIS) DALAM PENGEMBANGAN DESA WISATA TAJUK SEBAGAI KAWASAN EKOWISATA - HawikErvina I,; Efriyani Sumastuti,; Heri Prabowo,; Dhea Rizky A, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This community service is carried out with the aim of providing assistance to members of the tourism awareness group in Tajuk Village, Getasan District, Semarang Regency, regarding ecotourism management, which includes the concept of ecotourism, governance, physical maintenance of ecotourism, promotion and analysis of community resource potential. The method used in this activity is by direct socialization to the community and FGD (Focus Group Discussion). The targets of this service activity are members of the Tajuk Village Tourism Awareness Group (POKDARWIS), who are actively involved in managing the tourist village. The Tourism Awareness Group was given training, socialization, assistance and empowerment regarding ecotourism management. The results of this service show excellent motivation from the tourism conscious group in planning ecotourism management, developing ecotourism through fulfilling facilities according to needs, maintaining tourism assets, and promoting and empowering the economy of the community around tourist attractions.